Application of Cardiac Troponin in Cardiovascular Diseases Other Than Acute Coronary Syndrome. (6th January 2020) - Eggers, Kai M; Lindahl, Bertil
Abstract: BACKGROUND: Increased cardiac troponin concentrations in acute coronary syndrome (ACS) identify patients with ongoing cardiomyocyte necrosis who are at increased risk. However, with the use of more precise assays, cardiac troponin increases are commonly noted in other cardiovascular conditions as well. This has generated interest in the use of cardiac troponin for prognostic assessment and clinical management of these patients. In this review, we have summarized the data from studies investigating the implications of cardiac troponin concentrations in various acute and chronic conditions beyond ACS, i.e., heart failure, myocarditis, Takotsubo cardiomyopathy, aortic dissection, supraventricular arrhythmias, valve disease, pulmonary arterial hypertension, stroke, and in the perioperative setting. CONTENT: Cardiac troponin concentrations are often detectable and frankly increased in non-ACS conditions, in particular when measured with high-sensitivity (hs) assays. With the exception of myocarditis and Takotsubo cardiomyopathy, cardiac troponin concentrations carry strong prognostic information, mainly with respect to mortality, or incipient and/or worsening heart failure. Studies investigating the prognostic benefit associated with cardiac troponin–guided treatments however, are almost lacking and the potential role of cardiac troponin in the management of non-ACS conditions is not defined. SUMMARY: Increased cardiac troponin indicates increased risk for adverse outcome in patients with various cardiovascular conditions beyond ACS. Routine measurement of cardiac troponin concentrations can however, not be generally recommended unless there is a suspicion of ACS. Nonetheless, any finding of an increased cardiac troponin concentration in a patient without ACS should at least prompt the search for possible underlying conditions and these should be managed meticulously according to current guidelines to improve outcome.